A robust second‐generation genome‐wide test for fetal aneuploidy based on shotgun sequencing cell‐free DNA in maternal blood. (3rd May 2013) - Guex, N.; Iseli, C.; Syngelaki, A.; Deluen, C.; Pescia, G.; Nicolaides, K. H.; Xenarios, I.; Conrad, B.
Abstract : What's already known about this topic? Non‐invasive genome‐wide screening of fetal aneuploidy by shotgun sequencing cell‐free DNA in maternal blood has been shown to effectively identify fetal trisomy 21, but the performance of screening for other aneuploidies is variable. What does this study add? Optimizing all individual steps in the procedure and performing rigorous quality control provides a test capable of replacing invasive testing for the major aneuploidies.